Between Cyborg and Larva: A Vicious Circle That Human Beings Experience in the Post-humanist Era - Chukurov, Andrey (Slavica, 2018)
The article reveals the reasons for and specific features of the transition to the posthumanist era. The author of the study reviews the criticism of classical humanism and analyzes the relationship between the concepts of "trans-humanism" and "post-humanism." In a situation in which a permanent identity is impossible and people move to a “current” “unstable” identity, the Imaginary becomes the main guideline for the self-identification process. Human beings are unable to cope with the challenges of our time and are aware of their own inferiority. That is why they are trying to improve themselves through the available body modifications. However, this process gives them a new panic attack over the potential loss of control over the body. Analyzing these processes, the author turns to the most controversial and specific phenomenon of popular culture – "body horror". This genre reveals the deep layers of consciousness, fears and insecurity of human beings in the post-humanist era.